The Impact of Stunted Nutritional Status on Children’s Intelligence Levels in Disaster-Prone Areas - Fitraniar, Iin; Yusnaini, Yusnaini; Kartinazahri, Kartinazahri (Poltekkes Kemenkes Semarang, 2024)
Background: The nutritional problems arising post-disaster in Aceh Jaya Regency include health crises such as the cessation of healthcare services, casualties, and injuries among refugees. Other factors contributing to nutritional issues include the availability of clean water, environmental sanitation, and infectious diseases. Disasters create emergency situations that potentially lead to food and nutrition crises. The aim of this research is to investigate the impact of children with stunted nutritional status on the intelligence levels of children in disaster-prone areas. Methode: This study employs an observational research design with a cross-sectional approach. Data collection took place from July 24th to 27th, 2023, in the Sampoinet sub-district of Aceh Jaya Regency, Aceh Province. The sample size was determined to be 92 individuals using purposive sampling technique. Instruments used to measure children's nutritional status include a portable standing height measurement tool (stadiometer), while intelligence assessment of students was conducted using the CPM (Coloured Progressive Matrices) test. Bivariate data analysis was carried out using the chi-square statistical test with a confidence interval of 95%. Results: The study findings indicate that female children are more likely to have below-average intelligence levels (38.3%) compared to male children with the same intelligence level (22.2%). However, statistical analysis results show no significant relationship between gender and intelligence level. Furthermore, 57.1% of stunted children have below-average intelligence levels compared to children with normal nutrition with the same intelligence level (22.5%). Statistical analysis results indicate that stunted children have an impact on intelligence level (p=0.009). Conclusion: Stunted nutritional status has an impact on the intelligence level of school-age children in the Sampoinet sub-district of Aceh Jaya Regency.